Relationship between the dietary inflammation index and hypertension in American children and adolescents: findings from the national health and nutrition examination survey 1999–2018 - Lanfei Du; Jinxia Hao; Kai Yu; Peihong Su; Jie Pu; Zhiguo Tang; Fuqiang Liu; Jie Zhou (BMC Cardiovascular Disorders)
Abstract This study aimed to examine the relationship between the dietary inflammatory index (DII) and hypertension in children and adolescents using data from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999 and 2018. The analysis included 18,460 participants aged 8 to 17 years, with 2,070 diagnosed with youth hypertension, defined as blood pressure above the 95th percentile for their age and gender. Dietary information was collected to calculate the DII, which was initially treated as a continuous variable and later categorized into tertiles. Multivariable weighted logistic regression and restricted cubic spline (RCS) analyses were conducted to explore the association between DII and youth hypertension. The results revealed a positive relationship between higher DII scores and increased likelihood of hypertension in youth, with both regression and RCS analyses showing a linear positive correlation after adjusting for potential confounders. The findings suggest that managing dietary inflammation may be an important strategy for preventing hypertension in children and adolescents.